Microdomain forming proteins in oncogenesis - I. B. Zborovskaya; S. A. Galetskiy; A. V. Komel’kov (Успехи молекулярной онкологии, 2016)
Lipid rafts are lateral assembles of cholesterol, sphingomyelin, glicosphingolipids and specific proteins within cell plasma membrane. These microdomains are involved into a number of important cellular processes including membrane rearrangement, protein internalization, signal transduction, entry of viruses into the cell. Some of lipid rafts are stabilized by special microdomain-forming proteins such as caveolins, SPFH domain containing superfamily, tetraspanins, galectins, which maintain integrity of rafts and regulate signal transduction via forming of “signalosomes”. Involvement of the different lipid rafts is necessary in many situations such as binding of growth factors with their receptors, integrin regulation, cytoskeleton and extracellular matrix rearrangements, vesicular transport, etc. However, such classes of microdomain-forming proteins are still considered separately from each other. In this review we tried to perform complex analysis of microdomain-forming proteins in regulation of cancer assotiated processes.